A pixel counting based method for designing shading devices in buildings considering energy efficiency, daylight use and fading protection. (15th March 2020) - de Almeida Rocha, Ana Paula; Reynoso-Meza, Gilberto; Oliveira, Ricardo C.L.F.; Mendes, Nathan
Highlights: A multi-criteria method for designing shading devices of buildings is presented. The method is based on: search of non-dominated solutions and physical programming. Physical programming allows finding a ranking containing the preferred solutions. Design objectives are related to Energy Efficiency, Daylighting and Fading Protection. A Pixel Counting based tool allows evaluating more complex shading devices. Abstract: Multi-criteria design techniques applied to the analysis of shading devices of buildings have arisen as useful tools for architects. Even though several techniques have been applied to shading devices with simple geometries, they usually require numerous simulations to suitably complete the analysis, making the optimization process time-consuming. Since shading devices should prevent damage to furnishings and materials, performance indicators may not be related exclusively to thermal comfort, energy consumption and daylight performance, but also to other important criteria, such as fading protection. To overcome these limitations, this study aims to present a multi-criteria method for the design of shading devices, including fading protection as an evaluation criterion, regardless of geometry complexity. The method is applied to perforated shading devices of a room office, considering as the design objectives the energy savings, daylight availability on the work plane and solar beam incidence on interior surfaces. As a novelty, a more practical approach is proposed based on two main steps: search process, for obtaining a set of non-dominated solutions, and physical programming method, in which the solutions are ranked according to the preferences of decision makers. Besides, the solar beam incidence on interior surfaces is evaluated by using a pixel counting based method, which was emerged as a powerful algorithm due its capacity to simulate any geometry with accuracy and low computational cost. The results have shown that the proposed method is an effective process in designing of the optimal shading devices to reduce energy consumption, and improve the daylight use and the fading protection, regardless of the geometry complexity.